Management pain and anxiety in endodontic treatment - Andi Sumidarti; Wahyuni S. Dwiandhany (Journal of Dentomaxillofacial Science, 2017)
Objective : Dental pain is a common symptom that most often causes patient to seek dentist. A survey conducted by the American Association of Endodontics revealed that more than half patients who come to dentist have experienced pain, which originate from the teeth or of the surrounding tissue, can causes difficulties in handling, also the anxiety of the patient. Understanding the pain experienced by patient will help dentist to determine when to make an action. Most patient being fear with pain, so they delay to get treatment from dentist, and lead to the development of further infection and inflammation. The aim of this paper is to improve the understanding of pharmacology and procedures for pain and anxiety management in endodontic treatment. So, it is important to determine accurate diagnosis, management and drug administration.